Assessing Ex Ante the Poverty and Distributional Impact of the Global Crisis in a Developing Country : A Micro-simulation Approach with Application to Bangladesh - Habib, Bilal; Narayan, Ambar; Olivieri, Sergio; Sanchez-Paramo, Carolina (2012)
Measuring the poverty and distributional impact of the global crisis for developing countries is not easy, given the multiple channels of impact and the limited availability of real-time data. Commonly-used approaches are of limited use in addressing questions like who are being affected by the crisis and by how much, and who are vulnerable to falling into poverty if the crisis deepens? This paper develops a simple micro-simulation method, modifying models from existing economic literature, to measure the poverty and distributional impact of macroeconomic shocks by linking macro projections with pre-crisis household data. The approach is then applied to Bangladesh to assess the potential impact of the slowdown on poverty and income distribution across different groups and regions. A validation exercise using past data from Bangladesh finds that the model generates projections that compare well with actual estimates from household data. The results can inform the design of crisis monitoring tools and policies in Bangladesh, and also illustrate the kind of analysis that is possible in other developing countries with similar data availability.